The indirect impact of COVID-19 on child health - Ashikkali, Loucia (Paediatr Child Health (Oxford), 2020)
Since the detection of COVID-19 in December 2019, the rapid spread of the disease worldwide has led to a new pandemic, with the number of infected individuals and deaths rising daily. Early experience shows that it predominantly affects older age groups with children and young adults being generally more resilient to more severe disease.1, 2, 3 From a health standpoint, children and young people are less directly affected than adults and presentation of the disease has shown different characteristics. Nonetheless, COVID-19 has had severe repercussions on children and young people. These indirect, downstream implications should not be ignored. An understanding of the issues is essential for those who hope to advocate effectively for children to prevent irreversible damage to the adults of the future. This article reviews some of the evidence of harm to children that may accrue indirectly as a result of pandemics. It explores the physical and psychological effects, discusses the role of parenting and education, offering practical advice about how best to provide support as a healthcare professional.